New Strategy for the Synthesis of (±) Cherylline Dimethyl Ether - Venugopal, S.; Ramanatham, J.; Devanna, N.; Sanjeev Kumar, A.; Ghosh, Samir; Soundararajan, R.; Kale, Bhima; Mehta, G.N. (Asian Journal of Chemistry, 2010)
A concise route for the synthesis of (±) cherylline dimethyl ether is reported. The key steps involved are Grignard addition of 3,4-dimethoxy benzene magnesium bromide to the p-methoxy nitrostyrene, reduction of nitro intermediate followed by Pictet-Spangler cyclization.